Everybody cooks rice - Dooley, Norah; Thornton, Peter, 1956- (Minneapolis : Carolrhoda, 1991)
A child is sent to find a younger brother at dinnertime and is introduced to a variety of cultures through encountering the many different ways rice is prepared at the different households visited.
School Library Journal, November 1997.
Book Links (A.L.A.), February 2002.
Publisher's Weekly, February 1999.
Booklist, March 1993.
New York Times, September 1999.
Horn Book, March 1995.
Keywords: Cooking (Rice) -- Juvenile fiction; Cooking (Rice) -- Fiction; Cooking -- Rice -- Fiction; Cooking -- Rice